Evaluasi Pelaksanaan Pembelajaran Blended learning Pada Mata Pelajaran Alat Ukur dan Pengukuran - Tri Monica Audina; Fivia Eliza (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2023)
— Padang State University in the learning process has used blended learning. Blended learning is a form of learning that combines face-to-face learning with online learning that utilizes the role of technology. Along with the growing role of technology in the world of education, it cannot be abandoned, so that the most effective blended learning method in the world of information technology education is only a means to help smooth the learning process, especially in the form of finding learning resources, but does not completely replace the position and function of a person's role. Educators who provide knowledge and guidance through interaction for students. Through blended learning the learning process is not 100% carried out online, but is used to facilitate the face-to-face learning process in class if the material provided in class has not been delivered and can be accessed online. With blended learning facilities students can learn more freely, because students can interact easily with educators and obtain sources of information or teaching materials both inside and outside the classroom. The platform that can be used for blended learning at Padang State University is E-learning. Therefore, the purpose of this study is to find out how blended learning is applied to measurement subjects and measuring instruments. This research method is quantitative with context and input evaluation methods. The research subjects were students of the Electrical Engineering Education study program class of 2020. Data collection was carried out through a questionnaire or questionnaire with a Likert scale, while the tests carried out included validity tests, reliability tests and data analysis using average values, standard deviation values ​​and determining how much data which will be used score categories 1 to 5. The results showed that of the 9 indicators there is one indicator with an average value of 3.44 which is categorized as good enough, and 8 indicators are in the good category, so it can be concluded that overall it can be categorized as good with an average value of 3.98. From the results of the study it can be concluded that the application of blended learning in the course of measuring instruments and measurements on the context component on campus questions has provided adequate facilities and campus environment for blended learning. However, there is something that needs to be re-evaluated, such as holding socialization about the purpose of implementing blended learning. While the input component has been implemented properly.